Respostas

2013-11-26T01:33:13-02:00
Entao acho q e assim 

x²-8x+15=0                       =-(-8)+-raiz de 4      =8+-2  =
delta=b²-4*a*c                            2*1                   2
=(-8)²-4*1*15                         x'=8+2=5    x''=8-2=3
=64-60                                       2                2        
=4
X=-b+-raiz de delta                      entao acho q e assim 
           2*a
2013-11-26T01:52:14-02:00
X² - 8x + 15 = 0
a = 1               b = - 8               c = 15
∆ = b² - 4 . a . c 
∆ = (- 8)² - 4 * 1 * 15
∆ = 64 - 60
∆ = 4
x = - b +/- √∆
           2a
x = - (- 8) +/- 
√4
            2 * 1
x = 8 +/- 2
         2
x' = 8 + 2 
         2
x' = 10 
÷ 2
x' = 5

x" = 8 - 2 
          2
x" = 6 
÷ 2
x" = 3

Resposta: {5, 3}